Webquest “Educational path. revolution” as a gamified tool for teaching pedagogy: implementation design and pilot evaluation - Babenko, Sofiia; Vasilchuk, Viatcheslav; Yermolenko, Volodymyr O; Sidachenko, Vitalii; Yushko, Alisa; Nalyvaiko, Oleksii (Educological discourse, 2026)
The article presents the results of the development and pilot testing of the author’s multi-user webquest "Educational Path. Revolution", intended for studying the history of pedagogy, theory and methods of education, as well as pedagogical communication in higher education institutions. The relevance of the study is due to the growing role of digital and gamified forms of learning in higher education, especially in the conditions of a blended and distance education process. The purpose of the work is to describe the design of the implementation of the webquest and the initial evaluation of its perceived didactic value. The study was carried out in the design-based research format, which combined the stages of conceptualization, iterative design, technical implementation and product testing in real conditions of an educational session. 14 higher education applicants from the Faculty of Psychology of V. N. Karazin Kharkiv National University participated in the pilot study. An author’s questionnaire with 6 quantitative indicators and an open question was used for evaluation. The results showed high levels of cognitive interest (M = 4.6), task clarity (M = 4.6), and intention to reuse the product (M = 4.7). The lowest level was related to the effectiveness of team interaction (M = 3.0), which indicates the need for further development of cooperative mechanics. The practical significance of the study is to substantiate the possibilities of using a webquest as an interactive digital tool to increase student engagement, activate cognitive activity, and diversify teaching methods of pedagogical disciplines. The conclusion is made about the conceptual potential of a webquest as a tool for increasing engagement, supporting learning motivation, and meaningful learning of pedagogical material.